A historical Critical Reading in the Memoirs Of El Hadj Ahmed Sharif El Zahar Captain Of Algeria’s Ashraf - Nemir, Hocine (Journal of Human Sciences, 2025)
This paper deals with an important source of history of Algeria during the Ottoman period, namely the memoirs of Haj Ahmed to Sharif al-Zahar Naqib Achraf in Algiers, which chronicles the last phase of the Ottoman presence in Algeria and the beginning of the French occupation. The importance of this study lies in the fact that the author is an eyewitness to historical events and facts because of the social status he has received in Algerian society as Captain of Algerian supervision as well as the administrative positions assigned to him, which helped him in the transmission of historical events. This book was an honest mirror that removed the mystery of the fact of the Ottoman presence in Algeria during the recent period and through this paper we will try to introduce its owner and stand on its content, and know its method of writing, and mention some of the insults around it as well as show its importance in proportion to the history of modern Algeria.